Teachers’ Soft Skills on Students’ Science Process Capabilities and Academic Performance - Jonathan P Mellona (Integrated Science Education Journal, 2026)
Purpose of the study: This study aimed to determine the influence of the teachers’ soft skills on science process capabilities and academic performance of grade 11 students in public high schools in clusters IV and V during the S.Y. 2021 – 2022. This study also sought to determine the significant difference between the science process capabilities and academic performance of male and female grade 11 students in Earth and Life Science. Methodology: Explanatory sequential research design was utilized. The respondents included 33 science teachers and 376 grade 11 students. Data were collected through validated surveys, observation checklists, academic records, and interviews. Analysis was conducted using statistical software for quantitative data and thematic review for qualitative responses. Main Findings: Teachers strongly utilized their soft skills. Students demonstrated effective science process capabilities. Academic performance in Science was outstanding. No significant difference in science process capabilities between male and female students. However, female students performed better academically in Earth and Life Science. Moreover, significant positive relationships were found between teachers’ soft skills and students’ science process capabilities and academic performance. Novelty/Originality of this study: This study highlights the impact of teachers’ soft skills on both science process capabilities and academic performance in the new normal. Moreover, this study contributes to the limited empirical evidence linking teachers’ soft skills with both science process capabilities and academic performance in the post-pandemic blended learning context, offering insights for enhancing teaching strategies and professional development in senior high school science education.